Some properties of white and torrefied pellets obtained from oil palm trunk as raw material - Aujchariya Chotikhun; Jitralada Kittijaruwattana; Yutthapong Pianroj; Onder Tor; Emre Birinci; Pongsak Hengniran; Seng Hua Lee (BioResources, 2022)
Properties of unheated wood pellets were compared with those of torrefied wood pellets that had been heated to 270, 290, and 310 °C, with raw material taken from two different height levels of oil palm trunk (OPT). The gross calorific value, moisture content, ash content, volatile matter, fixed carbon, density, and weight loss were examined. Air drying or oven drying pretreatment was applied to the raw materials. The results showed that the heating values of samples increased when raw materials were torrefied, depending on the heat treatment temperature. The torrefied pellets were improved by as much as 66.4% in heating value compared with OPT pellet samples. The greatest improvement was found in torrefied pellet samples prepared at 310 °C, using air drying, and height levels of OPT between 0.3 to 1.5 m. The ash content of samples tended to increase when the torrefied temperature was increased, while the volatile matter value was reduced with high temperature. Based on the findings, OPT could be used as a raw material to produce value-added white and torrefied pellets as sustainable solid biofuel.
Keywords: heating value; torrefied pellet; volatile matter; oil palm trunk; wood pellet; TP248.13-248.65; Biotechnology; 6. Clean water; 12. Responsible consumption